2012
DOI: 10.3390/ijms131114889
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Lipase Production by Burkholderia sp. Using Response Surface Methodology

Abstract: Response surface methodology (RSM) was employed to optimize the extracellular lipase production by Burkholderia sp. HL-10. Preliminary tests showed that olive oil, tryptone and Tween-80 exhibited significant effects on the lipase production. The optimum concentrations of these three components were determined using a faced-centered central composite design (FCCCD). The analysis of variance revealed that the established model was significant (p < 0.01). The optimized medium containing 0.65% olive oil (v/v), 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…In a similar study, Lo et al [26] reported the overwhelming effect of tryptone on the lipase activity from Burkholderia specie. Tryptone is seldom reported as optimum organic nitrogen source, only other reported [25,31].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a similar study, Lo et al [26] reported the overwhelming effect of tryptone on the lipase activity from Burkholderia specie. Tryptone is seldom reported as optimum organic nitrogen source, only other reported [25,31].…”
Section: Discussionmentioning
confidence: 94%
“…Lipase activity of lipase obtained from Burkholderia sp. in the presence of olive oil and at 30°C was 122.3 U/mL [26]. Rajendran et al [27] identified a strain of Bacillus brevis capable to secrete alkaline lipase and its lipase activity increased to 5.1 U/mL after optimization of the culture medium.…”
Section: Discussionmentioning
confidence: 98%
“…We obtained 10-fold higher enzyme activity by such optimization. Previously, statistical optimization studies have been carried out using Moritella sp., [17] Burkholeria sp., [16] Pseudomonas sp., [29] and Geotrichum sp. [30] Overall, 2.6-to 6.0-fold increases in lipolytic enzyme production were obtained compared to that observed before optimization.…”
Section: Enhanced Production Of Cold-active Lipasementioning
confidence: 99%
“…[25][26][27][28] The medium components affecting the production of lipolytic enzyme were optimized using statistical design. There have been several reports that some complex nitrogen sources stimulate lipase production: soybean meal, [17] tryptone, [16] yeast extract, [25] and peptone. [27] In our case, yeast extract showed the most positive effect on lipolytic enzyme production.…”
Section: Enhanced Production Of Cold-active Lipasementioning
confidence: 99%
See 1 more Smart Citation